Peruvian post democratic transition audiovisual: from images of Marcha de los Cuatro Suyos to Vladivideos parody - Delgado Chumpitazi, Mónica (2021)
This article explores the importance of TV archives as device of the Peruvian documentaries produced at the beginning of the 21st century, in relation to the social and political context of the democratic transition after a crisis of governance. Also some uses of analogic video and other digital supports, like journalistic archive as technology of memory.